Gender and Urban Studies as an Interactive Approach and Integrated Curriculum (Journal of the College of Education for Women, 2022)
The integration of gender in urban studies is considered a goal and objective to build a society characterized by justice and equality. It further allows all its residents to enjoy the opportunities to live in a safe urban life. Based on the that, the limitations of the research and its field of interest related to the relationship between gender and urban studies have become clear. The insufficient knowledge in this regard considers gender as a concept that does not exist in itself, but rather overlaps and intersects with several concepts and studies, including urban studies. Thus, it has become necessary to adopt a descriptive methodology that helps reach a theoretical framework to explain the beginnings of such an interaction and integration between the two concepts. Such a step in return helps clarify the chronology of a number of conferences and their role in shedding light on gender issues focusing on the 2030 agenda. This is because such agenda is related to the near future and obligates all countries to achieve their goals where gender is one of them. Accordingly, the present work poses the question: Are gender studies and urban studies reciprocal and collaborative? The research ends with a set of conclusions, such as: the gender analysis of urban issues provides new insights and an explicit introduction to the study of gender and its effects in urban studies. They further illustrate the role of such insights on the development and prosperity of these cities to be suitable for all. The research has recommended integrating gender-sensitive planning strategies, as they represent a key factor to policy makers, urban planners, and designers in their policies, programs and decision-making processes. They also help create a sustainable and inclusive urban development.